Nabokov's 'Diabolical Task': Translation as Capture and Becoming-Butterfly. - Larson, K. Maya (Deleuze & Guattari Studies, 2020)
The lepidopteral imaginary that animates Nabokov's relationship to translation can be understood in light of Deleuze and Guattari's notions of 'apparatus of capture' and 'rhizomatic becomings'. On the one hand, Nabokov's scientific fascination with butterflies frames his radically literal approach to translation. The scientific dissection of texts and butterflies 'captures' an original and singular content as it flutters, reducing it to the homogenised content of a target source. On the other hand, in Speak, Memory's engagement with 'multiple metamorphoses, familiar to butterflies', Nabokov as both literary artist and autobiographical personage becomes-butterfly with translation itself, entering into affective intensities with butterflies that include lepidopteral relations of movement and rest, speed and slowness.